2021
DOI: 10.3390/atmos12010083
|View full text |Cite
|
Sign up to set email alerts
|

Co-Seismic Ionospheric Disturbance with Alaska Strike-Slip Mw7.9 Earthquake on 23 January 2018 Monitored by GPS

Abstract: The Mw7.9 Alaska earthquake at 09:31:40 UTC on 23 January 2018 occurred as the result of strike slip faulting within the shallow lithosphere of the Pacific plate. Global positioning system (GPS) data were used to calculate the slant total electron contents above the epicenter. The singular spectrum analysis (SSA) method was used to extract detailed ionospheric disturbance information, and to monitor the co-seismic ionospheric disturbances (CIDs) of the Alaska earthquake. The results show that the near-field CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Therefore, the SSA method enables data-adaptive filtering (Rekapalli et al, 2014). In a recent study, Zhang et al (2021) discussed the robustness of the SSA-based filtering approach to suppress the signal leakage of CIDs. They suggested that the SSA filtering is beneficial to detect the small amplitude CIDs associated with the strike-slip earthquakes.…”
Section: Filtering Methods Used In the Studymentioning
confidence: 99%
“…Therefore, the SSA method enables data-adaptive filtering (Rekapalli et al, 2014). In a recent study, Zhang et al (2021) discussed the robustness of the SSA-based filtering approach to suppress the signal leakage of CIDs. They suggested that the SSA filtering is beneficial to detect the small amplitude CIDs associated with the strike-slip earthquakes.…”
Section: Filtering Methods Used In the Studymentioning
confidence: 99%
“…We use the length of 63 days to do SSA and use 60 days to analyze so that it is consistent with the previous results. Some researcher used the different data length to do analyze, depending on their own demand (Shi et al, 2020;Zhang et al, 2021). Next, we create a trajectory matrix with a window length of 20 days for each dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The appearance of this local electric field anomaly leads to changes in the electron density, ion composition, and electron temperature of the ionosphere. From an acoustic point of view [47], in the seismically active zone, the sound wave is disturbed by the gravitational vibration to produce an AGW (Acoustic Gravity Wave), which continues to propagate upward, resulting in the enhancement of gravitational waves and planetary waves, disturbing the ionosphere, and changing the ionosphere and the density of the plasma. From a mechanical point of view [48], in the seismogenic zone, due to the plate tectonics of the crust, the amplitude of gravity oscillations caused by seismic activity increases with the height from the ground.…”
Section: Seismo-ionospheric Monitoring Mechanismmentioning
confidence: 99%